Cooperative financial evaluation using altman z-score to identifying financial distress - Fredy Olimsar; Ismail Mokoagow; Fransisca Dyah Anggraini; Herry Mokoginta; Moch Natsir Syafarin Mokoginta (Jurnal Mantik, 2023)
Cooperatives have become an essential form of economic organization throughout the world, providing their members with a vast array of services and benefits. Nonetheless, economic fluctuations and business insecurity can place many cooperatives in a financial bind. Therefore, a thorough financial evaluation is required to identify potential issues and implement preventative measures. This research examines Karya Mandiri Cooperative as an illustration of an at-risk savings and loan cooperative. This study employs the Modified Altman Z-Score model to identify cooperatives experiencing financial distress. Using financial statements from 2020 to 2022, the Modified Altman Z-Score Method on cooperative financial statements yields safe prediction results. The predicted Z value between 2020 and 2022 has increased from 6.76 in 2020 to 8.33 in 2022. The assessment of the cooperative's health level demonstrates a significant shift from 2020, resulting in a cut-off value of 6.76 and a classification as "quite healthy" in terms of cooperative health, to 2021, resulting in a cut-off value of 7.79 and a classification as "quite healthy" in terms of cooperative health, and to 2022, resulting in a cut-off value of 8.33 and a classification as "healthy" in terms of cooperative health.